2016
DOI: 10.2147/ott.s98363
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of icotinib as first-line therapy in patients with advanced non-small-cell lung cancer

Abstract: Background and objectiveSeveral clinical trials have proven that icotinib hydrochloride, a novel epidermal growth factor receptor (EGFR)–tyrosine kinase inhibitor, exhibits encouraging efficacy and tolerability in patients with advanced non-small-cell lung cancer (NSCLC) who failed previous chemotherapy. This study was performed to assess the efficacy and toxicity of icotinib as first-line therapy for patients with advanced pulmonary adenocarcinoma with EGFR-sensitive mutation.Patients and methodsThirty-five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In the IPASS [4], OPTIMAL [11], WJTOG34O5 [6], NEJ002 [12], and EURAC [13] clinical studies, gefitinib or erlotinib yielded a prolonged median PFS compared with chemotherapy (9.2-13.1 months versus 4.6-6.3 months) and an increased response rate (64%-82% versus 30.7-47.3%) compared with chemotherapy for patients with sensitive EGFR mutations. Meanwhile, the efficacy of icotinib in this study is similar to previous retrospective studies, which showed an ORR of 48.6%-66.7%, a DCR of 94.4-95.6%, a median PFS of 11.0-14.9 months, and a median OS of 21.0-37.0 months [14,15].…”
Section: Discussionsupporting
confidence: 88%
“…In the IPASS [4], OPTIMAL [11], WJTOG34O5 [6], NEJ002 [12], and EURAC [13] clinical studies, gefitinib or erlotinib yielded a prolonged median PFS compared with chemotherapy (9.2-13.1 months versus 4.6-6.3 months) and an increased response rate (64%-82% versus 30.7-47.3%) compared with chemotherapy for patients with sensitive EGFR mutations. Meanwhile, the efficacy of icotinib in this study is similar to previous retrospective studies, which showed an ORR of 48.6%-66.7%, a DCR of 94.4-95.6%, a median PFS of 11.0-14.9 months, and a median OS of 21.0-37.0 months [14,15].…”
Section: Discussionsupporting
confidence: 88%
“…Icotinib is a novel EGFR‐TKI approved for the second‐ or third‐line treatment of advanced NSCLC by the State Food and Drug Administration of the People's Republic of China . Preclinical data on the ability of icotinib to cross the BBB are lacking; however, CSF penetration in patients with brain metastases from NSCLC has been reported as 1.2%–9.7% across three different dose levels (125–500 mg), with a significant correlation between icotinib concentration in the CSF and plasma .…”
Section: Egfr‐tkismentioning
confidence: 99%
“…Many retrospective and prospective studies, as well as meta-analyses, that have studied NSCLC patients with various lines of EGFR-TKI treatment have demonstrated longer progression-free survival (PFS) and occasionally more favorable overall survival (OS) in those with Del19 than in those with the L858R or other mutations (6)(7)(8). In contrast, other clinical studies, including phase III trials, have demonstrated no difference in the efficacy of EGFR-TKI treatment according to the EGFR mutation type (9)(10)(11)(12). Therefore, whether there are differences in survival between patients with these common EGFR mutations remains controversial.…”
Section: Introductionmentioning
confidence: 99%